Strategi Pembelajaran Tutor dalam Meningkatkan Motivasi Belajar Peserta Didik Paket C pada Program Pembelajaran Komunitas di PKBM Kak Seto Surabaya - Su’udy, Mohammad Luqman; Soedjarwo, Soedjarwo (J+PLUS UNESA, 2023)
community and is focused on life skills or life skills to be able to improve their respective living standards. Tutors here play an important role in non-formal education, with tutors providing the teaching materials needed in order to achieve the planned learning objectives. This aims to help students to understand the content of learning and can be applied in everyday life, tutors are also expected to carry out effective, good, and meaningful teaching in each lesson. Providing good teaching will create comfort to learners, providing effective teaching can also convince learners and will strengthen memory to learners. This research uses a qualitative approach. The subjects in this study were the head tutor, package C tutors, and package C community program students at PKBM Kak Seto Surabaya. Data collection used is using interviews, observation and documentation. The techniques used in data analysis are data condensation, data presentation, and conclusion drawing. After that, the truth value is tested using the methods of credibility, dependability, confirmability and transferability. The result of this research is that the motivation of package C community learning students increases, it is proven that after the learning strategy is carried out by tutors, students are faster in understanding the subject matter. Supporting factors in this study are appropriate and adequate facilities and infrastructure as well as tutors who are competent in their fields.